A Comparative Analysis of AES and LWE in Digital Image Encryption - Aisyah Nooravieta Setiawan; Siska Dwi Kumala; Aisyah Enggel Luthfiyah (Griya Journal of Mathematics Education and Application, 2026)
This study investigates a comparative analysis between two cryptographic algorithms, which are the Advanced Encryption Standard (AES) and the Learning With Errors (LWE), in the case of digital image encryption. The core of the aim is to evaluate the computational performance, output quality, and security of the two algorithms when applied to digital image data. The methods used include measuring the computational performance by recording the encryption and decryption times for both algorithms, as well as performing a detailed analysis of the image quality post-decryption, and comparing the security of the two algorithms. The results of this analysis indicate that AES outperforms LWE in terms of speed, providing faster encryption and decryption processes with minimal impact on image quality. However, LWE offers a stronger level of security against quantum-based attacks, although with a longer processing time. This study provides important insights for selecting the appropriate encryption algorithm based on security and performance requirements in digital image processing